Papaína imobilizada em partículas magnéticas: novos modelos de triagem de ligantes - Leandro, Cleiton Silva (2019)
Cathepsins, human lysosomal enzymes, are associated with the development of various diseases, and cruzaine is an important enzyme in the development of the protozoan Trypanosoma cruzi, causes Chagas' disease. Cysteine proteases, cathepsins and cruzaine, are known as papain-like, due to their structural similarities and catalytic mechanism. Papain is a commercial enzyme, inexpensive and stable, and thus, it has been used as a model for screening assays for cysteine-proteases’ ligands. As the classical assays for these enzymes are spectrophotometrically-based, herein a direct method for measuring the enzymatic product of the reaction using liquid chromatography hyphenated to mass spectrometry is described. For that, new reaction conditions were employed. Under this condition, in solution papain showed a KM of 52.9 ± 3.12 μM. For developing new assay conditions and considering the advantages of use of immobilized enzymes, papain was covalently immobilized on to magnetic particles (P-MB), producing a bioreactor with a KM of 34.9 ± 3.59 μM. For qualifying P-PB screening assay, 10 known cysteine protease inhibitors including acridones, quinolinones, flavonoids, and dipeptidyl nitriles were screened. Maltose was used as a non-binder of papain. With the exception of maltose that showed no inhibitory capacity, in the solution assay (2,1 x 10-3 U) the percentage of inhibition ranged from 13 to 100%, while with P-MBs (1,4 x 10-3 U) the inhibition range was from 34 to 85%. Ligand Fishing assay, papain bioreactors showed affinity for all known binders of cysteine proteases, and no affinity for maltose. Six of them presented expressive affinity only ratio for the active P-MB, with no retention to inactive P-MB control. The other four binders varied their affinity ratio in the range of 2.0 to 3.5. With the ethanolic extract from the stem of Melia azedarach, 11 compounds were fished, among them catechin and epicatechin. The results herein described demonstrates that papain bioreactors can be used for screening cysteine-proteases’ ligands.